BENTUK-BENTUK SARKASME DALAM TUTURAN REMAJA DI JAGAKARSA - Khalisa Humaira, Alma; Puspita, Erina (STKIP Subang, 2026)
Sarcasm is a form of harsh language that can be found in various circles, such as among teenagers and adults. Many people use sarcasm to communicate, including the residents of the Jagakarsa, South Jakarta, where the majority of teenagers use sarcasm in their daily communication. This research aims to identify the forms and functions of sarcasm used in the speech of teenagers in Jagakarsa, South Jakarta. This research uses the observation and note-taking method where the researcher listens attentively and records what is said in the conversation. The results show the presence of two forms of sarcasm used, namely coarse sarcasm and subtle sarcasm. The function of sarcasm in the speech of Jagakarsa teenagers is used for mockery, insinuation, jokes, and expression of anger. This finding shows a change in the function of language in line with the times.